PEMBERIAN KOMPENSASI UANG PESANGON TERHADAP TENAGA KERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU - Michele Fedryca; Gunardi Lie (Fakultas Hukum Universitas Tarumanagara, 2021)
An employment agreement is an agreement that occurs between workers and employers in written form that contains points of the rights and obligations of both parties in accordance with applicable laws. The agreement is made between the Employer and the Worker. In its arrangement, the employment agreement is divided into an indefinite employment agreement with a fixed term employment agreement. Both agreements relate to employee status. Where the status of employees concerns their rights as workers. One of them includes severance pay. In the world of work, it is not uncommon to find inconsistencies in the rights and obligations of both employers and workers. In this writing, the author finds several things that cause the non-fulfillment of labor rights that are not given fairly by the employer.